ANALYSIS ON LINKAGE AND MULTIPLIER EFFECTS OF UPSTREAM OIL AND GAS SECTOR IN INDONESIA'S ECONOMY USING INPUT-OUTPUT METHOD - pri agung rakhmanto; Komaidi Notonegoro; Rini Setiati; Dwi Atty Mardiana (Scientific Contributions Oil and Gas, 2025)
The aim of this study is to analyze the role of the upstream oil and gas sector within Indonesia's economy in terms of its linkage to other sectors and the multiplier effect it produces. The input-output (IO) analysis method is applied by calculating the total, backward, and forward linkage index and multiplier effect index values of the upstream oil and gas sector. Building upon a previous study using the 2005 BPS IO Database updated in 2010 (2005 IO), this study used the 2010 IO Database released by BPS in 2015 (2010 IO) and the 2016 IO Database released in 2021 (2016 IO), processing the data using Python-based software. Based on the calculation using 2010 IO Database, there were 93 sectors with linkage to the upstream oil sector and 104 with linkage to the upstream gas sector, whereas the 2016 IO Database identified 96 sectors with linkage to the upstream oil sector and 113 with linkage to the upstream gas sector. Simulated calculation and analysis results revealed that there was an increase in total (backward and forward) linkage index values of the upstream oil and gas sector, from 3.8801 to 4.0826 for the upstream oil sector and from 3.1256 to 3.3940 for the upstream gas sector. In regard with multiplier effect, simulated calculation results also pointed towards an increase in total multiplier index values, from 6.1855 to 7.8943 for the upstream oil sector and from 4.9828 to 6.5630 for the upstream gas sector. The increase in total multiplier index in the national upstream oil and gas sector correlates with an increase in linkage between the upstream oil and gas sector and other sectors in Indonesia's economy as a whole, both backward and forward. Analysis results showed that the greater the multiplier index reported by a sector with linkage to the upstream oil and gas sector, the greater the total multiplier index produced in the upstream oil and gas sector.